Searching the SN 1987A SETI Ellipsoid with TESS - Bárbara Cabrales; James R. A. Davenport; Sofia Sheikh; Steve Croft; Andrew P. V. Siemion; Daniel Giles; Ann Marie Cody (The Astronomical Journal, 2024)
The SETI Ellipsoid is a strategy for technosignature candidate selection that assumes that extraterrestrial civilizations who have observed a galactic-scale event—such as supernova 1987A—may use it as a Schelling point to broadcast synchronized signals indicating their presence. Continuous wide-field surveys of the sky offer a powerful new opportunity to look for these signals, compensating for the uncertainty in their estimated time of arrival. We explore sources in the TESS continuous viewing zone, which corresponds to 5% of all TESS data, observed during the first 3 yr of the mission. Using improved 3D locations for stars from Gaia Early Data Release 3, we identified 32 SN 1987A SETI Ellipsoid targets in the TESS continuous viewing zone with uncertainties better than 0.5 lt-yr. We examined the TESS light curves of these stars during the Ellipsoid crossing event and found no anomalous signatures. We discuss ways to expand this methodology to other surveys, more targets, and different potential signal types.